Pengaruh identitas merek, lokasi dan harga terhadap keputusan wisatawan menginap di bliss surfer legian kuta bali - Imaniar, Nasdya; Arismayanti, Ni Ketut; Widyatmaja, I Gusti Ngurah (Jurnal Kepariwisataan dan Hospitalitas; Vol 3 No 2 (2019): Vol.3,No.2,2019, 2019)
Abstract This research is motivated by the decrease in tourist occupancy rates at Bliss Surfer Hotel Bali in the last 5 recent years amid rising levels of tourist visits to Bali and the number of guest comments about the selection of hotels with the most results on location and price but the selection of less desirable concepts in this thematic hotel. The purpose of this study is to find out the effect of brand identity, location and price partially and simultaneously on the decision of tourists to stay at Bliss Surfer Hotel Bali. The sample technique used was purposive sampling and collected sample techniques using accidental sampling on 100 hotel travelers staying at Bliss Surfer Hotel Bali. The data analysis techniques used are validity test, reliability test, classic assumption test, multiple regression analysis, multiple correlation analysis, analysis of determination coefficient, hypothesis test and likert scale. The results of this reasearch found that each brand identity independent variable (X 1 ), location (X 2 ) and price (X 3 ) together had a significant effect on the fixed variable tourist decision (Y). Based on F test, it can be obtained that F count results are greater than F table (58,382 greater than 2,76). Brand identity variables on the decision of tourists to stay partially obtained significant results with a variable significance value of 0.000 <? 0.025 and t count value 4.213> t table 1.984. Location variables on the decision of tourists to stay partially obtained significant results with a variable significance value of 0.000 where <? 0,025 and t count 6,677> t table 1,984. Price variables on the decision of tourists to stay partially obtained significant results with a variable significance value of 0.000 <? 0.025 and a value of t count 3.675> t table 1.984. The dominant variable in this study is the location variable with a partial correlation value of the brand identity (X 1 ) of r = 0.585, partial correlation of location (X 2 ) of r = 0.703, and partial correlation of price (X 3 ) of r = 0.567.   Keywords: brand identity, location, price, decision of tourists to stay